Pengolahan Kekayaan Sumber Daya Intelektual Menggunakan Teknologi Knowledge Management - Febrian Wahyu Christanto (Jurnal Transformatika, 2015)
The most important asset in the modern management science is the human resource that can generate knowledge that can be used to maintain the stability of the company in case of regeneration of labor in a company. Problems arise because the majority of knowledge in a company is Tacit knowledge that stored in the brain workforce of experience gained during the work, while Explicit knowledge is only a fraction of the knowledge that can be poured into a medium. Knowledge is very important to use to achieve success and maintain the stability of the company. With the Knowledge Management technology, it is expected that the need for knowledge and Intellectual Property Resources of the operations of a company can be used safely, quickly, easily, and inexpensively